O Colégio Notre Dame e as adaptações à política educacional (1937-1942) - Bonato, Belady (2010)
During the Estado Novo (1937-1945) the regulation of education was carried out from 1942, with the Reformation Capanema, under the name of Organic Laws of Teaching. Capanema was aimed at the formation of the personality of the adolescent and selection by cultivation of ancient and modern humanities and thereby raise the young patriotic consciousness and humanistic conscience. Attention should be paid to the details of the attempted formation of the consciousness of the young through education focused on patriotism. Given this context, we will work in the College Notre Dame de Passo Fundo-RS, analyzing their attitude to the reforms and trying to identify through the documents provided by the college what mechanisms used to fit with the legal reform of secondary education